Serbia : Access to Justice for Poor Women and Men - Decker, Klaus; Harley, Georgia; Svircev, Srdjan (World Bank, Washington, DC, 2015)
This report aims at identifying the particular needs and constraints faced by the poorest women and men when accessing the judicial system. Similarly to the Judicial Functional Review,6 the scope of this report focuses primarily on the courts because they are the main vehicle for justice service delivery and the primary institutions of justice in Serbia. The scope includes all types of services and covers litigious and non-litigious aspects of civil, commercial, administrative, and criminal justice. The focus is on the actual implementation and day-to-day functioning of the sector institutions that deliver justice to people, rather than the law on the books . The scope includes other institutions in the sector to the extent that they enable or impede service delivery by the courts, including: the Ministry of Justice (MOJ), the High Judicial Council (HJC), the State Prosecutorial Council (SPC), the courts, the Public Prosecutor Offices (PPOs), the Judicial Academy, the Ombudsperson s Office, the police, prisons, and justice sector professional organizations (such as the Bar, notaries, bailiffs, and mediators). The focus of this report is on access to justice services, including relevant financial, informational, and geographic barriers to such access.